2023
DOI: 10.1055/a-2075-2725
|View full text |Cite
|
Sign up to set email alerts
|

Fäkaler Mikrobiota-Transfer (FMT) in Deutschland – Status und Perspektive

Abstract: Zusammenfassung Einführung Der Fäkale Mikrobiota-Transfer (FMT) ist eine Behandlung zur Modulation der gastrointestinalen Mikrobiota. Der Einsatz bei rezidivierender Clostridioides-difficile-Infektion (rCDI) ist europaweit etabliert und wird in nationalen und internationalen Leitlinien empfohlen. Der FMT ist in Deutschland im Fallpauschalensystem der Krankenhäuser kodierfähig. Eine auf dieser Kodierung basierende umfassende Erhebung zur Häufigkeit des Einsatzes fehlt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Regarding the number of FMT procedures in Germany, a recent study analyzing reports from the Institute for Hospital Remuneration (InEK), the Federal Statistical Office (DESTATIS), and hospital quality reports revealed that only 293 FMTs were coded annually by 175 different hospitals between 2016 and 2018. This was followed by a steady decline in subsequent years, with only 119 FMTs recorded in 2021 [39]. This decline is likely partly explained by COVID restrictions, which hindered stool donor recruitment.…”
Section: Fmt As a Successful Intervention For Preventing Rcdimentioning
confidence: 99%
“…Regarding the number of FMT procedures in Germany, a recent study analyzing reports from the Institute for Hospital Remuneration (InEK), the Federal Statistical Office (DESTATIS), and hospital quality reports revealed that only 293 FMTs were coded annually by 175 different hospitals between 2016 and 2018. This was followed by a steady decline in subsequent years, with only 119 FMTs recorded in 2021 [39]. This decline is likely partly explained by COVID restrictions, which hindered stool donor recruitment.…”
Section: Fmt As a Successful Intervention For Preventing Rcdimentioning
confidence: 99%
“…Auch die Standardisierung der Durchführung des FMT in Leitlinien und die Aufklärung der Patienten/-innen über die Optionen eines FMT erhielten hohe Wertungen. Die aktuelle regulatorische Problematik des FMT in Deutschland als nicht zugelassenes Arzneimittel ist Gegenstand intensiver Diskussionen [26,27]; es zeichnet sich noch keine Lösung ab. 2021 erhielten laut genanntem US-Survey 1,5 % der Patienten/-innen einen FMT; in Deutschland waren es bei hospitalisierten Patienten/-innen mit einer CDI (Haupt-und Nebendiagnose) lediglich 0,2 % [24,27].…”
Section: Diskussionunclassified
“…Die aktuelle regulatorische Problematik des FMT in Deutschland als nicht zugelassenes Arzneimittel ist Gegenstand intensiver Diskussionen [26,27]; es zeichnet sich noch keine Lösung ab. 2021 erhielten laut genanntem US-Survey 1,5 % der Patienten/-innen einen FMT; in Deutschland waren es bei hospitalisierten Patienten/-innen mit einer CDI (Haupt-und Nebendiagnose) lediglich 0,2 % [24,27]. Im englischen NHS wird der FMT explizit gefördert [28] und europaweit regelhaft eingesetzt [29].…”
Section: Diskussionunclassified